Investigation of the Status of the Wooden Pallet Market during the COVD-19 Pandemic - Sean Hobbs; Laszlo Horvath; Brad Gething (BioResources)
It is estimated that there are 3.1 billion pallets in circulation in the United States, and the majority of these pallets are made of wood. This research was conducted to obtain important information about the market and raw material usage trends in the wooden pallet and container industry from 2019 through 2021. The results revealed that the wooden pallet and container industry produced an estimated 919 million new pallets in 2021, which is an estimated 75% increase over 2016. The 48” x 40” pallet size continued to be the dominant new pallet size with a 29% market share. The share of softwood lumber used in the industry has steadily increased since 2016, and it accounted for 81% of the lumber used in pallet production in 2021. The industry used 38% of the total sawn softwood and hardwood lumber produced in the U.S. The industry also produced 280 million repaired and remanufactured pallets; this is a 16.4% decrease compared to 2016. Approximately 22% of respondents stated that they were not affected by the pandemic. A majority of respondents (51%) stated that they exceeded their 2019 sales, and only 12% saw no change in sales in 2020 compared to 2019.